Management Guidance Counseling Im-proving Students' Digital Literature Knowledge - Mawarny*, Endah; Yunus, Yunus (Riwayat: Educational Journal of History and Humanities, 2023)
This study aims to determine the condition of students' digital literacy related to the obstacles and solutions found in the implementation of guidance related to increasing students' digital literacy at SMK Sandikta Bekasi City. This research is a qualitative research that uses a phenomenological approach. Sources of data, namely primary data sourced from school principals, BK teachers, students. Meanwhile, secondary data were taken from documents related to the research. The instrument used in collecting data is the researcher himself who functions to determine and select informants as data sources, analyze data, interpret data, and the instruments in collecting data are observation, interviews, and documentation. The results showed that guidance and counseling was carried out with systematic management starting from planning, organizing, implementing, and supervising, which in the management process was carried out by prioritizing coordination and communication by all school members in integrating behavioral education in daily activities. Guidance and counseling management improves students' digital literacy in designing objectives, materials, strategies and evaluation of learning.